Study guides

☆☆

Q: Which expression is equivalent to 3x - 3y?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

3x-3y?

solve -3x-3y=-15

Radical (3x) = radical(x) * radical(3).

3x - 4y = 8Solve for x:3x = 4y + 8x = 4/3y + 8/3Solve for y:-4y = -3x + 8y = 3/4x - 2

This is like aÂ² - bÂ², with a = 9xÂ² and b = 9yÂ². This can be factored as (a - b)(a + b), then substitute for a & b: (9xÂ² - 9yÂ²)(9xÂ² + 9yÂ²), then (9xÂ² - 9yÂ²) can factor to (3x - 3y)(3x + 3y) so we have: (3x - 3y)(3x + 3y)(9xÂ² + 9yÂ²)

Related questions

3x-3y?

6

3x + 3x + 3x = 3* (3x) = 9x

It is an expression that is equivalent to -3x-19.

3x plus 2y - 3 is an expression. There can be no answer to one expression and one linear equation in two variables.

The equivalent expression of 3x-9 plus 3x plus 5 is negative 4.

There is not an answer but you can factor it.3x+3y=3(x+y)

solve -3x-3y=-15

The slope is -1. 3x+3y=12 Subtract 3x 3y=-3x+12 Divide by 3 y=-x+4

Radical (3x) = radical(x) * radical(3).

2X + 3X + 3Y ???= 5X + 3Y===============yes, addition of these monomials yields that answer

1, 3, x, y, 3x, 3y, and xy are the factors of the expression 3xy

People also asked